2021
DOI: 10.3389/fimmu.2021.634152
|View full text |Cite
|
Sign up to set email alerts
|

Differentially Expressed Genes in Hepatopancreas of Acute Hepatopancreatic Necrosis Disease Tolerant and Susceptible Shrimp (Penaeus vannamei)

Abstract: Acute hepatopancreatic necrosis disease (AHPND) is a lethal disease in marine shrimp that has caused large-scale mortalities in shrimp aquaculture in Asia and the Americas. The etiologic agent is a pathogenic Vibrio sp. carrying binary toxin genes, pirA and pirB in plasmid DNA. Developing AHPND tolerant shrimp lines is one of the prophylactic approaches to combat this disease. A selected genetic line of Penaeus vannamei was found to be tolerant to AHPND during screening for disease resistance. The mRNA express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
9
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 60 publications
4
9
0
Order By: Relevance
“…Meanwhile, the top 10 gene sets enriched in resistant families in the GSEA were all involved in energy metabolism process. The finding was consistent with the previous report that SP and ChyB had a significantly higher expression level in resistant shrimp line during the AHPND infection (Mai et al, 2021). Several studies have indicated that metabolic processes such as lipid metabolism and carbohydrate metabolic process in shrimp were greatly affected during AHPND infection (Velazquez-Lizarraga et al, 2019;Kumar et al, 2021).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Meanwhile, the top 10 gene sets enriched in resistant families in the GSEA were all involved in energy metabolism process. The finding was consistent with the previous report that SP and ChyB had a significantly higher expression level in resistant shrimp line during the AHPND infection (Mai et al, 2021). Several studies have indicated that metabolic processes such as lipid metabolism and carbohydrate metabolic process in shrimp were greatly affected during AHPND infection (Velazquez-Lizarraga et al, 2019;Kumar et al, 2021).…”
Section: Discussionsupporting
confidence: 92%
“…In this study, several genes in proPO activation system showed a higher expression level in the susceptible families. A previous report showed that PPAE2 presented a higher expression level in the susceptible line of L. vannamei after AHPND challenge in comparison with the resistant line (Mai et al, 2021). This system is important for fighting against bacteria pathogens in penaeid shrimp (Amparyup, et al, 2013), and the increased activity of proPO system against Vibrio has been reported in Fenneropenaeus indicus (Sarathi et al, 2007), L. vannamei (Boonchuen et al, 2021), and Macrobrachium rosenbergii (Rao et al, 2015).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Recently, studies have shown that the interaction between immunity and metabolism seems to participate in shrimp’s response to AHPND [ 29 ]. However, transcriptome studies of shrimp responses to AHPND have mainly focused on immune-related genes and pathways, and little is known about metabolism-related changes [ 16 , 30 , 31 , 32 ]. Here, the comparative transcriptome study mainly focused on the metabolic processes in shrimp hepatopancreas at different time points post V. parahaemolyticus infection.…”
Section: Discussionmentioning
confidence: 99%
“…The variation of disease-resistant ability could be reflected by differential expression of genes at the background level. In P. vannamei, several genes including chymotrypsin A, serine protease, crustin-P and prophenol oxidase activation system 2 showed differential expression levels between VpAHPND tolerant and susceptible populations [9]. A transcriptomic comparison between three VpAHPND resistant and three susceptible families identified 489 differentially expressed genes (DEGs) in L. vannamei and 19 tested genes also showed different expression in their offspring [10].…”
Section: Introductionmentioning
confidence: 99%